PERANCANGAN APLIKASI TIKET IT HELPDESK UNTUK MENINGKATKAN EFEKTIVITAS LAYANAN TEKNOLOGI INFORMASI - karwur, veron vaskarian; Ramdha Janur Andriadji; Alviatul Laila; Fahmi Junaedi; Rocci Samuel Mossad; Riyan Latifahul Hasanah; Nugraha, Siti Nurhasanah (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2025)
Effective and responsive Information Technology (IT) services play a crucial role in supporting organizational operations. However, in practice, ASPAN Company still faces challenges in recording, monitoring, and resolving IT incidents due to the absence of an integrated system. This study aims to design an IT Helpdesk ticketing application that enhances the effectiveness of IT services through a systematic, fast, and measurable incident management process. The research adopts the waterfall methodology and qualitative data collection using a case study approach through direct observation involving IT staff and service users. The result of this study is a web-based application that enables users to create incident report tickets, track ticket status, and provide feedback on the services received. The system also provides performance reports that are useful for service evaluation. The implementation results demonstrate a significant improvement in IT service performance, where the average incident resolution time decreased from 2.5 hours to 1.5 hours. Furthermore, the system facilitates real-time ticket tracking, historical issue management, and structured performance reporting to support IT service evaluation. With the implementation of the IT Helpdesk ticketing application, the IT issue-handling process becomes more efficient, well-documented, and ultimately improves the overall quality of Information Technology services within ASPAN company